Numerical Data Concerning the Sensitivity of Anaerobic Bacteria to Oxygen - Fredette, V. (1967)
Upon comparison of results obtained from growing eight different species of anaerobic bacteria in deep agar under two and three atm of pure oxygen with results of growing them in air under atomospheric pressure, it appears possible that the old terms of “microaerophobic,” “very strict anaerobe,” and “microaerophilic” can be replaced by precise values corresponding to the size of the inhibition zone produced by oxygen under various pressures when the bacteria are grown in a solid medium. The simultaneous effect of the dilution of the inoculum and the pressure of oxygen used was determined with the help of an electronic computer according to the standard multiple regression method. Two indices have been worked out which express the sensitivity of the species at different oxygen pressures when varying numbers of anaerobic bacteria are used: X sp, which is the size in millimeters of the inhibition zone when 1:10 dilutions of the culture are grown under pure oxygen at atmospheric pressure (lp=0), and B sp, which is the result of multiplying by 1.43 the difference in size of inhibition zone when 1:10 dilutions of the culture are grown under atmospheric air (lp = −0.7) and under pure oxygen at 1 atm absolute.